COVID-19 in unvaccinated patients with inborn errors of immunity—polish experience - Kołtan, Sylwia; Ziętkiewicz, Marcin; Grześk, Elżbieta; Becht, Rafał; Berdej-Szczot, Elżbieta; Cienkusz, Magdalena; Ewertowska, Marlena; Heropolitańska-Pliszka, Edyta; Krysiak, Natalia; Lewandowicz-Uszyńska, Aleksandra; Mach-Tomalska, Monika; Matyja-Bednarczyk, Aleksandra; et al. (Frontiers in Immunology, 2022)
At the beginning of the SARS CoV-2 pandemic, patients with inborn errors of immunity (IEI) appeared to be particularly vulnerable to a severe course of the disease. It quickly turned out that only some IEI groups are associated with a high risk of severe infection. However, data on the course of COVID-19 in patients with IEI is still insufficient, especially in children, hence further analyzes are required. The retrospective study included 155 unvaccinated people with IEI: 105 children and 50 adults (67,7% and 32.3%, respectively). Male patients dominated in the study group (94 people, 60.6%). At least two comorbidities were found in 50 patients (32.3%), significantly more often in adults (56% vs.21%). Adult patient presented significantly more COVID-19 symptoms. Asymptomatic and mildly symptomatic course of COVID-19 was demonstrated in 74.8% of the entire group, significantly more often in children (88.6% vs 46%). Moderate and severe course dominated in adults (54% vs 11.4%). Systemic antibiotic therapy was used the most frequently, especially in adults (60% vs 14.3%).COVID-19-specific therapy was used almost exclusively in adults. In the whole group, complications occurred in 14.2% of patients, significantly more often in adults (30% vs 6.7%). In the pediatric group, there were 2 cases (1.9%) of multisystem inflammatory syndrome in children (MIS-C). Deaths were reported only in the adult population and accounted for 3.9 % of the entire study group. The death rate for all adults was 12%, 15.4% for adults diagnosed with common variable immunodeficiency (CVID), 12.5% for those with X-linked agammaglobulinemia (XLA) and 21.4% for patients with multimorbidity. The results of our study implies that vaccinations against COVID-19 should be recommended both for children and adults with IEI. Post-exposure prophylaxis and early antiviral and anti-SARS-CoV-2 antibody-based therapies should be considered in adults with IEI, especially in those with severe humoral immune deficiencies and comorbidity.